2005
DOI: 10.1002/art.21111
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular free radical production in synovial T lymphocytes from patients with rheumatoid arthritis

Abstract: Objective. To investigate the cellular and molecular sources of oxidative stress in patients with rheumatoid arthritis (RA) through analysis of the production of reactive oxygen species (ROS) in synovium.Methods. Cytochemical procedures based on the 3,3-diaminobenzidine (DAB)-Mn 2؉ deposition technique were used on unfixed cryostat sections of synovium from RA patients and rheumatic disease controls. For immunophenotyping, sections were incubated, fixed, and stained with fluorescein isothiocyanatelabeled antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 16 publications
1
45
1
Order By: Relevance
“…Although others reported expression of a functional NADPH oxidase complex in T cells (21,22), we could detect neither Ncf1 expression nor oxidative burst in T cells from our rats or mice. We do not exclude the occurrence of constitutive low levels of ROS in T cells (23), but the very low background ROS levels we observed did not differ between T cells derived from the different animal strains and thus seem to be NADPH oxidase independent. This observation leads to the hypothesis that the number of T cell surface ϪSH groups is determined by other cells that do produce ROS, such as APCs or neutrophils (24).…”
Section: Discussioncontrasting
confidence: 67%
“…Although others reported expression of a functional NADPH oxidase complex in T cells (21,22), we could detect neither Ncf1 expression nor oxidative burst in T cells from our rats or mice. We do not exclude the occurrence of constitutive low levels of ROS in T cells (23), but the very low background ROS levels we observed did not differ between T cells derived from the different animal strains and thus seem to be NADPH oxidase independent. This observation leads to the hypothesis that the number of T cell surface ϪSH groups is determined by other cells that do produce ROS, such as APCs or neutrophils (24).…”
Section: Discussioncontrasting
confidence: 67%
“…We have recently demonstrated that oxidative stress in T lymphocytes from the synovial fluid (SF) (24) and synovial tissue (25) of RA patients is a result of T cell-intrinsic intracellular ROS production. Persistent ROS production in RA SF T cells correlates with constitutive activation of the small GTPase Ras, and blocks activation of the related GTPase Rap1 (24).…”
Section: Synovial Adherent Cells and This Correlated With T Cell Mitmentioning
confidence: 99%
“…It is known that neutrophil granulocytes, macrophages and lymphocytes are activated, so that reactive oxygen and nitrogen species (RS) are produced. These RS can react with lipid, protein and nucleic acids and are thought to be of importance for the etiology and chronicity of the inflammatory rheumatic diseases [8]. One approach to counteract this oxidative stress situation is the use of antioxidants as therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%